PENGARUH TEKNIK BIOLOGIC NURTURING BABY LED FEEDING DAN FINGER HOLD TERHADAP PERUBAHAN RASA NYERI PADA IBU POST SECTIO DI RS X DI DENPASAR - Rusmilawati, Ni Wayan; Wulandari, Made Ririn Sri; Agustini, I G Ayu Ratih; Purnamayanthi, Pande Putu Indah (Journal of Advanced Nursing and Health Sciences, 2021)
Maternal health services begin during pregnancy, one of which is delivery by means of cesarean section. The problem that occurs post sectio caesarea is pain. Management to reduce post sectio caesarean pain is recommended by finger hold relaxation. The relaxation technique that is also recommended for mothers after partum sectio caesarean is breastfeeding with the biological nurturing position of the baby led feeding. The purpose of this study was to determine the effect of biologic nurturing baby led feeding and finger hold techniques on changes in pain in post sectio caesarean mothers.This research is a true experimental quantitative research with a pretest - posttest design with control. The sampling technique used in this study is probability sampling by simple random sampling. The number of samples in this study were 36 people who were divided into two groups, namely the control group as many as 18 people and the treatment group as many as 18 people who had met the inclusion and exclusion criteria. Analysis of data using the Mann-Whitney U test analysis. The results of the Mann-Whitney U test analysis showed that the p value was 0.000 (<0,05), meaning that the hypothesis of this study was accepted, which means that there was an effect of biological nurturing baby led feeding and finger hold techniques on changes in pain in post-sectio caesarean mothers. The results of this study are expected to be used as a reference in providing nursing care so that it can improve the quality of post-caesarean post section maternal services in dealing with pain experienced.